Characterization of Human Osteoarthritic Cartilage Using Optical and Magnetic Resonance Imaging - Jones, Ella F. (Springer-Verlag, 2011)
PURPOSE: Osteoarthritis (OA) is a degenerative disease starting with key molecular events that ultimately lead to the breakdown of the cartilage. The purpose of this study is to use two imaging methods that are sensitive to molecular and macromolecular changes in OA to better characterize the disease process in human osteoarthritic cartilage. PROCEDURES: Human femoral condyles were collected from patients diagnosed with severe OA during total knee replacement surgeries. T (1ρ) and T (2) magnetic resonance measurements were obtained using a 3-Tesla whole body scanner to assess macromolecular changes in the damaged cartilage matrix. Optical imaging was performed on specimens treated with MMPSense 680 to assess the matrix metalloproteinase (MMP) activity. A linear regression model was used to assess the correlation of MMP optical data with T (1ρ) magnetic resonance (MR) measurements. Slices from a representative specimen were removed from regions with high and low optical signals for subsequent histological analysis. RESULTS: All specimens exhibit high T (1ρ) and T (2) measurements in the range of 48–75 ms and 36–69 ms, respectively. They also show intense photon signals (0.376 to 7.89 × 10(−4) cm(2)) from the activated MMPSense 680 probe, indicative of high MMP activity. The analysis of variance test of the regression model indicates a positive correlation between the MMP optical signal and T (1ρ) measurements (R (2) = 0.8936, P = 0.0044). Histological data also confirmed that regions with high MMP optical signal and intense T (1ρ) relaxation exhibit severe clefting, abnormal tidemarks, and irregular cellularity. CONCLUSIONS: The high T (1ρ) and T (2) measurements suggest that there is a severe loss of proteoglycans with high water mobility in the damaged cartilage. The intense optical signals found in these specimens indicate the presence of active MMPs, and the positive correlation with T (1ρ) measurements implicates MMP’s involvement in OA progression, characterized by a severe loss of proteoglycans in the cartilage matrix. The bimodal approach using optical and MR imaging may provide key molecular and macromolecular information of the disease pathway, offering insights toward the development of new tools for the early detection, treatment, and/or prevention of OA.